Experience of using advagraf after kidney transplantation in the Sklifosofsky Research Institute for Emergency Medicine - A. V. Pinchuk; B. V. Shmarin; R. V. Storojev; A. G. Balkarov; I. V. Dmitriev; E. M. Balakirev (Трансплантология (Москва))
The efficiency of the advagraf as the main immunosuppressant in renal transplant recipients in the early postoperative period has been assessed. A good tolerability of the medicament has been confirmed. Satisfactory performance of renal graft function recovery after surgery was marked. Recommendations on the use of the advagraf in the early terms after kidney transplantation, including a condition of a violation of the gastrointestinal tract function.